Upaya Guru Tahfiz Dalam Meningkatkan Karakter Cinta Al-Qur’an Pada Santri Di Pondok Pesantren Sirojuddin Sidabowa, Banyumas - Ani, Arimbi; Rohman, Mujibur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research is based on the consequences of educational failure that causes moral decline and damage to the character of the younger generation. As a form of character formation in accordance with the values of the Islamic religion, it must be guided by religion and adhere to the Qur'an. As a form of character formation in accordance with the values of the Islamic religion, it must be guided by religion and adhere to the Qur'an. Without the Qur'an, humans will live without direction. For this reason, it is necessary to increase the character of love for the Qur'an, especially the younger generation. The Sirojuddin Sidabowa Islamic Boarding School, Banyumas has improved the character of love for the Qur'an in students by implementing a tahfiz program. Previous research has discussed more about the formation of the Qur'an's love character, but there are still few studies that focus on the efforts of tahfiz teachers in improving the character of love for the Qur’an in students at Islamic boarding school. Therefore, the main problem researched in this study is how the tahfiz teacher's efforts in improving the character of love for the Qur'an in students at the Sirojuddin Sidabowa Islamic Boarding School, Banyumas. This study aims to describe and analyze how the efforts of tahfiz teachers in improving the character of love for the Qur'an in students. This study uses a descriptive qualitative method. Data were collected through semi-structured interviews, observations, and documentation. Data is analyzed through data reduction methods, data presentation, conclusion making and data validity tests. The results of the study show that the indicators of love for the Qur'an in students are shown by several attitudes, namely: students feel calm and happy when reading the Qur'an; Students do not feel bored or bored reading the Qur'an; Feeling longing when far from the Qur'an; Obey all the commandments and prohibitions in the Qur'an.